Quantum dots, compositions containing the same, and display panels
By chemically cross-linking using ligands of phosphate or phosphite acrylates to lock the ligands on the surface of quantum dots, the problem of degradation and instability of quantum dots in inkjet printing ink is solved, and a quantum dot composition with high luminescence efficiency and long life is achieved.
Patent Information
- Application Number
- CN202510273710.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Quantum dots are prone to decrease efficiency and are unstable in inkjet printed, especially in high-polar acrylates, resulting in reduced fluorescence efficiency and short service life.
Quantum dots including a first ligand and a second ligand of a phosphate acrylate or a phosphite acrylate are used to improve stability and fluorescence efficiency by chemically cross-linking the ligand on the surface of the quantum dots.
It achieves high luminous efficiency and long life of quantum dots, can maintain good solubility and stability in high polar acrylates, and extend the service life of the display panel.
Smart Images

Figure SMS_45 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of quantum dots, and in particular, to a quantum dot and a composition and a display panel containing the quantum dot. Background Art
[0002] Quantum dot inks with different luminescent colors can be used to prepare color pixels of display panels. When preparing quantum dot inks for inkjet printing, in order to improve the compatibility of quantum dots in photocurable monomers (polarity), the surface ligands of quantum dots are usually exchanged to improve compatibility. However, after quantum dots are configured into inkjet printing inks, they are usually prone to reduced efficiency and become unstable. Common methods include adding stabilizing agents that isolate water and oxygen, free radical capture agents, etc. Summary of the invention
[0003] The purpose of the present disclosure is to provide a quantum dot and a composition and a display panel containing the same, so as to improve the blue light resistance of the quantum dot, stabilize the photoluminescence efficiency, and extend the service life of the display panel.
[0004] According to a first aspect of the present disclosure, a quantum dot is provided, the quantum dot comprising a first ligand and a second ligand; the first ligand is selected from one or both of phosphate acrylate and phosphite acrylate, the phosphate acrylate is represented by Chemical Formula 1, and the phosphite acrylate is represented by Chemical Formula 2; the second ligand comprises compounds represented by Chemical Formula 3 and Chemical Formula 4;
[0005] [Chemical formula 1]
[0006] ;
[0007] [Chemical formula 2]
[0008] ;
[0009] [Chemical formula 3]
[0010] ;
[0011] [Chemical formula 4]
[0012] ;
[0013] At least one of the above R1, R2, and R3 includes a polymer of a first acrylate, at least one of the above R4 and R5 includes a polymer of a second acrylate, the above R6 includes a polymer of a third acrylate, the above R7 is a group containing at least one ester bond, and the number of carbon atoms of R7 is 6 to 20; the number of units of the above first acrylate polymer, the above second acrylate polymer, and the above third acrylate polymer are independently selected from 2 to 10.
[0014] Optionally, the raw materials for preparing the above-mentioned phosphate acrylate include: phosphate with at least one hydroxyl group or phosphorus pentoxide or phosphorus oxychloride, monoacrylate containing one hydroxyl group and monoacrylate without other active functional groups; the raw materials for preparing the above-mentioned phosphite acrylate include: monophosphite with at least one hydroxyl group or phosphorus trichloride or phosphorous acid, the above-mentioned monoacrylate containing one hydroxyl group and the above-mentioned monoacrylate without other active functional groups.
[0015] Optionally, the monoacrylate containing one hydroxyl group is selected from propylene glycol monoacrylate, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 5-hydroxypentyl acrylate, and 2-hydroxyethyl acrylate; the monoacrylate without other active functional groups is selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, isopropyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, propyl methacrylate, butyl methacrylate, isobutyl methacrylate, lauryl methacrylate, tetrahydrofuranyl acrylate, 2-phenylethyl acrylate, 2-ethoxyethyl acrylate, glycidyl methacrylate, polyethylene glycol acrylate with a number average molecular weight of 200 to 400, ethoxyethoxyethyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, 1-adamantyl acrylate, 4-ethylphenyl acrylate, and 3-methoxybutyl acrylate.
[0016] Optionally, at least one of R1, R2, and R3 is a H atom, or R4 is a H atom.
[0017] Optionally, the organic substance of the above chemical formula 4 is selected from one or more of methacryloyloxyethyl succinate, acrylic acid dimer, mono(2-acryloylethyl ether)succinic acid, and mono-2-(methacryloyloxy)ethyl maleate.
[0018] Optionally, the molecular weights of the first ligand and the second ligand are independently selected from 200 to 2000; preferably, the quantum dots are cadmium-free quantum dots.
[0019] According to a second aspect of the present disclosure, a quantum dot composition is provided, wherein the quantum dot composition comprises quantum dots, and the quantum dots are the above-mentioned quantum dots.
[0020] Optionally, the quantum dot composition further includes an acrylate monomer, and the mass fraction of the quantum dots is 20-60%.
[0021] Optionally, the quantum dot composition further comprises a photoinitiator or a thermal initiator. Preferably, the viscosity of the quantum dot composition at 30° C. is less than 25 cP.
[0022] According to a third aspect of the present disclosure, a display panel is provided, wherein the display panel comprises a quantum dot layer, and the quantum dot layer is formed by curing the quantum dot composition.
[0023] In the above technical solution, the first and second ligands of the above quantum dots can react with the carbon-carbon double bond under light or heat conditions, so that the first ligand and the second ligand are chemically cross-linked on the surface of the quantum dots, locking the ligands on the surface of the quantum dots, better protecting the quantum dots, thereby achieving high luminous efficiency and long life of the display panel. The quantum dots with the above ligands have good solubility in highly polar acrylates, which is convenient for subsequent applications. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0025] Toluene or octane solutions of quantum dots are commonly used in this field to store quantum dots. However, in order to configure photocurable quantum dot ink, quantum dots need to be extracted from the aforementioned non-polar solvent. When used to configure quantum dot polar ink with a solid content (such as more than 30%), the quantum dots will have a process of precipitation and then redissolution. Usually in this process, the commonly used oleic acid ligands on the surface of quantum dots are easily reduced. The more the precipitation and redissolution processes of quantum dots (such as separation and purification) are, the oleic acid content gradually decreases with the number of times, the organic components on the surface of quantum dots decrease, and finally the efficiency of quantum dots in ink decreases. The inventors found that the ligand structure of phosphate and thiol groups has an unstable valence structure. Under ultraviolet or blue light excitation, it is easy to obtain free radicals and fall off from the surface of quantum dots, which reduces the fluorescence efficiency of quantum dots. Therefore, it is necessary to redesign the ligand to solve the above technical problems.
[0026] In a first aspect of the present disclosure, a quantum dot is provided, the quantum dot comprising a first ligand and a second ligand; the first ligand is selected from one or both of phosphate acrylate and phosphite acrylate, the phosphate acrylate is shown in Chemical Formula 1, and the phosphite acrylate is shown in Chemical Formula 2; the second ligand comprises compounds represented by Chemical Formula 3 and Chemical Formula 4;
[0027] [Chemical formula 1]
[0028] ;
[0029] [Chemical formula 2]
[0030] ;
[0031] [Chemical formula 3]
[0032] ;
[0033] [Chemical formula 4]
[0034] ;
[0035] At least one of R1, R2, and R3 includes a first acrylate oligomer, at least one of R4 and R5 includes a second acrylate oligomer, R6 includes a third acrylate oligomer, R7 is a group containing at least one ester bond, and the number of carbon atoms of R7 is 6 to 2; the number of units of the first acrylate oligomer, the second acrylate oligomer, and the third acrylate oligomer is independently selected from 2 to 10. The carboxyl group, phosphite group, phosphate group, and mercapto group in the above compounds are used for coordination with the surface of quantum dots. Acrylate oligomers contain repeating units, often containing long chains or branched compounds with ether bonds, ester bonds, and carbon-carbon double bonds, which improve the compatibility of quantum dots in subsequent applications in polar systems. The first and second ligands of the above quantum dots react with the carbon-carbon double bonds under light or heat conditions, so that the first ligand and the second ligand are chemically cross-linked on the surface of the quantum dots, locking the ligands on the surface of the quantum dots to better protect the quantum dots. Quantum dots with the above ligands have good solubility in highly polar acrylates.
[0036] In some embodiments, the R7 main chain is a carbon chain and further includes an ether bond or a double bond. In some embodiments, R7 does not include a group that can react with a quantum dot ligand, such as a hydroxyl group and an amino group.
[0037] In some embodiments, the raw materials for preparing phosphate ester acrylates include: phosphate esters or phosphorus pentoxide or phosphorus oxychloride with at least one hydroxyl group, monoacrylates containing one hydroxyl group, and monoacrylates without other active functional groups. The hydroxyl groups of the phosphate ester and the hydroxyl groups of the monoacrylate containing one hydroxyl group undergo dehydration condensation (phosphorus oxychloride and the monoacrylate containing one hydroxyl group react to remove HCl, and phosphorus pentoxide and the monoacrylate containing one hydroxyl group react to remove H2O), and the monoacrylate containing one hydroxyl group and the monoacrylate without other active functional groups undergo addition polymerization.
[0038] In some embodiments, the raw materials for preparing phosphite acrylates include: a monophosphite or phosphorus trichloride or phosphorous acid with at least one hydroxyl group, a monoacrylate containing a hydroxyl group, and a monoacrylate without other active functional groups. The hydroxyl group of the monophosphite and the hydroxyl group of the monoacrylate containing a hydroxyl group undergo dehydration condensation (HCl is removed after the reaction of phosphorus trichloride and the monoacrylate containing a hydroxyl group, and H2O is removed after the reaction of phosphorous acid and the monoacrylate containing a hydroxyl group), and the monoacrylate containing a hydroxyl group and the monoacrylate without other active functional groups undergo addition polymerization. In this application, "without other active functional groups" refers to functional groups that can be triggered by an initiator to become free radicals. Monoacrylates without other active functional groups can avoid cross-linking of the molecular chains of the polymerized product, making the polymerized product unable to dissolve in a good solvent.
[0039] The preparation of phosphate acrylate or phosphite acrylate is obtained under thermal initiation or photoinitiation.
[0040] In some embodiments, the monoacrylate containing one hydroxyl group is selected from propylene glycol monoacrylate, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 5-hydroxypentyl acrylate, and 2-hydroxyethyl acrylate; the monoacrylate without other active functional groups is selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, isopropyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, propyl 2-methacrylate, butyl methacrylate, isobutyl methacrylate, lauryl methacrylate, tetrahydrofuranyl acrylate, 2-phenylethyl acrylate, 2-ethoxyethyl acrylate, glycidyl methacrylate, polyethylene glycol acrylate with a number average molecular weight of 200 to 400, ethoxyethoxyethyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, 1-adamantyl acrylate, 4-ethylphenyl acrylate, and 3-methoxybutyl acrylate.
[0041] In some embodiments, when the phosphate and the phosphite monoester contain one hydroxyl group, the amount of the monoacrylate containing one hydroxyl group is 1-2 parts, and the amount of the monoacrylate without other active functional groups is 1-9 parts.
[0042] In some embodiments, when the phosphate and the phosphite monoester contain two hydroxyl groups, the amount of the monoacrylate containing one hydroxyl group is 2-4 parts by weight, and the amount of the monoacrylate without other active functional groups is 2-18 parts by weight.
[0043] In some embodiments, the raw materials for preparing the third acrylate oligomer include the monoacrylate without other active functional groups and the raw material with a thiol group, and the molar ratio of the monoacrylate without other active functional groups to the raw material with a thiol group is 1:(2~10).
[0044] In some preferred embodiments, there is no group in R1-R6 that coordinates with the quantum dots. Only one functional group in each of the first and second ligands interacts with the quantum dots, thereby preventing the quantum dots from agglomerating and affecting subsequent applications.
[0045] In some embodiments, at least one of R1, R2, R3 is a H atom, or R4 is a H atom.
[0046] In some embodiments, the organic compound of Chemical Formula 1 is selected from: , , ,
[0047] , , , , , , ,or , wherein n is 1 to 9. Preferably n is 2 to 4.
[0048] In some embodiments, the compound of Formula 2 is selected from:
[0049] , , , ,or
[0050] , wherein l is 1 to 9. Preferably l is 2 to 4.
[0051] In some embodiments, the compound of Formula 3 is selected from:
[0052] , , , , , , , ,or , wherein m is 1 to 9. Preferably m is 2 to 4.
[0053] In some embodiments, the synthesis method of the organic compound of Chemical Formula 3 is Raft chain transfer polymerization. The synthesis method can refer to the following documents: "Preparation and Dynamic Behavior of Polymer-based Molecular Cluster Nanocomposites Based on Electrostatic Effects" by He Dongrong; "The Effect of Temperature on TBTGA as Chain Transfer Agent...PMMA Relative Molecular Mass" by Wang Zhenbang, "Synthesis and Application of End-functionalized Polyisoprene Liquid Rubber Based on RAFT Polymerization" by Li Jun, and "Preparation of Macromolecular Emulsifier PAA-b-PMMA and Its Application in Emulsion Polymerization" by Wang Pengtao. In some specific embodiments, the Raft reagent is first synthesized: tert-butyl mercaptan and sodium hydroxide aqueous solution are added to distilled water. After mixing evenly and adding acetone, the entire container is placed in an ice water bath to cool down, and carbon disulfide is added while stirring to obtain an orange transparent solution. To the orange transparent solution, 2-bromopropionic acid and sodium hydroxide solution are added dropwise in sequence, and the reaction temperature is controlled to be below 30°C. After the reaction is stirred for 24 hours, concentrated hydrochloric acid is slowly added dropwise. Finally, the yellow product is filtered, washed with a large amount of water, and vacuum dried for standby use. Resynthesize the ligand: dissolve the acrylate monomer, Raft reagent, and initiator azobisisobutyronitrile in toluene, pass nitrogen for 15 minutes to remove oxygen from the system, and stir at 70°C for 6 hours. After the reactants are cooled, add excess n-hexylamine to partially aminolyze the trithiocarbonate to form a thiol group. Use cyclohexane to precipitate the product from toluene, rinse with ethanol several times, and finally dry to obtain a white product, i.e., the compound of chemical formula 3.
[0054] In some embodiments, the organic compound of Chemical Formula 4 is selected from one or more of methacryloyloxyethyl succinate, acrylic acid dimer, mono(2-acryloylethyl ether)succinic acid, and mono-2-(methacryloyloxy)ethyl maleate. The organic compound of Chemical Formula 4 can be purchased from the market.
[0055] In some embodiments, the molecular weights of the two organic substances of the first ligand and the second ligand are independently selected from 200 to 2000; the quantum dots having the above ligands are uniformly dispersed in monomers such as acrylate. If the molecular weight of the ligand is too large, when the quantum dot ligands are exchanged and formulated into a printable ink, the solid content of the quantum dot itself is low, resulting in poor fluorescence efficiency of the quantum dot layer after the quantum dot composition is cured.
[0056] In some embodiments, the quantum dots are cadmium-free quantum dots, meeting increasingly stringent environmental protection requirements.
[0057] In some preferred embodiments, during ligand exchange, the amount ratio of the first ligand added to the second ligand is 1:1 to 1:4. In some embodiments, during ligand exchange, in the second ligand added, the amount ratio of the compound represented by Chemical Formula 3 to the compound represented by Chemical Formula 4 is 1:1 to 1:4.
[0058] In some embodiments, the first ligand and the second ligand of the quantum dot are exchanged to the surface of the quantum dot in the same ligand exchange process. Since the terminal functional groups of the ligands have a strong interaction with the quantum dots, the overall ligand exchange time is short and thorough.
[0059] In a second aspect of the present disclosure, a quantum dot composition is provided. The quantum dot composition includes quantum dots, and the quantum dots are any one of the above-mentioned quantum dots.
[0060] In some embodiments, the quantum dot composition further comprises a monomer, which can be an acrylate. The acrylate is selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, isopropyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, propyl 2-methacrylate, butyl methacrylate, isobutyl methacrylate, lauryl methacrylate, tetrahydrofuranyl acrylate, 2-phenylethyl acrylate, 2-ethoxyethyl acrylate, glycidyl methacrylate, polyethylene glycol acrylate with a molecular weight of 200 to 400, ethoxyethoxyethyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, 1-adamantyl acrylate, 4-ethylphenyl acrylate, 3-methoxybutyl acrylate, triethylene glycol diacrylate, One or more of 1,6-hexanediol diacrylate, 1,4-phenylene diacrylate, 1,6-hexanediol ethoxylate diacrylate, 3-methyl-1,5-pentanediol diacrylate, cyclohexanedimethanol-1,4-diacrylate, triethylene glycol dimethacrylate, tetraethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, ethoxylated bisphenol A diacrylate, ethylene glycol diacrylate, di(ethylene glycol) diacrylate, butanediol diacrylate, ethylene glycol dimethacrylate, tetra(ethylene glycol) diacrylate, propoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, and di(trimethylolpropane) tetraacrylate.
[0061] In some embodiments, to achieve a corresponding light absorption and light extraction ratio, the mass fraction of quantum dots is 20-60%.
[0062] In some embodiments, the quantum dot composition further comprises a photoinitiator or a thermal initiator. The photoinitiator includes but is not limited to (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide. The thermal initiator includes but is not limited to azobisisobutyronitrile, dibenzoyl peroxide.
[0063] The above composition is suitable for inkjet printing. In some embodiments, the viscosity of the quantum dot composition at 30° C. is less than 25 cP. In the inkjet printing technology, the quantum dot layer is thin, and the above viscosity range can achieve long-term stable printing.
[0064] According to a third aspect of the present disclosure, a display panel is provided. The display panel includes a quantum dot layer. The quantum dot layer is formed by curing any one of the above-mentioned quantum dot compositions.
[0065] The above curing is thermal curing or photocuring. When the quantum dot composition is cured, the monomers (such as acrylate) in the quantum dot composition are prone to incomplete free radical polymerization, and the molecular weight increases sharply, so that the quantum dot composition is cured.
[0066] During the actual use of quantum dot compositions that are photocured into devices or used in display panels, due to the continuous activation of backlight (10-1000 nm) and the accumulation of water and oxygen content in the environment, the surface ligands are excited and converted to valence states. The ligands are prone to deterioration or shedding, resulting in a continuous weakening of the fluorescence efficiency of the quantum dots, which in turn affects the service life of the device or display panel.
[0067] With the above technical solution, the phosphate group or phosphite group of the first ligand, the thiol group or carbon-carbon double bond of the second ligand, and the carbon-carbon double bond on the monomer (acrylate) undergo a chemical reaction under the action of a thermal initiator or a photoinitiator. During the photocuring process of the quantum dot composition, or after the quantum dot composition is cured, the first and second ligands undergo chemical cross-linking on the surface of the quantum dot, locking the first ligand and the second ligand (coordinated or uncoordinated) on the surface of the quantum dot. Under ultraviolet or blue light excitation, the first ligand and the second ligand will not fall off due to a simple change in valence, thereby increasing the service life of the quantum dot layer and, in turn, the service life of the display panel.
[0068] The quantum dot layer can maintain an efficiency of more than 80% or more than 90% of the initial value for 2000 hours under high-intensity blue light irradiation (20,000 nit).
[0069] In some embodiments, the thickness of the quantum dot layer is 10 to 50 micrometers. In some embodiments, the quantum dot layer includes a red quantum dot layer and a green quantum dot layer.
[0070] Hereinafter, the embodiments are described in more detail with reference to specific examples. However, they are illustrative examples of the present disclosure, and the present disclosure is not limited thereto.
[0071] Example 1
[0072] Prepare the first ligand compound:
[0073] ;
[0074] Prepare the secondary ligand compound:
[0075] and (methacryloyloxyethyl succinate).
[0076] Ligand exchange: The toluene solution of CdSe / ZnSe / ZnS (PL peak wavelength: 633nm, half peak width 20.0nm, initial ligand is oleate) is precipitated with ethyl acetate and centrifuged to obtain quantum dot solid. It is put into a propylene glycol methyl ether acetate solution containing the first ligand and the second ligand, wherein the mass ratio of quantum dot solid: ligand: propylene glycol methyl ether acetate is 1:1:3, wherein the first ligand accounts for 10% of the mass of the whole ligand, and the second ligand methacryloyloxyethyl succinate accounts for 30% of the mass of the whole ligand. Stir for 6 hours to complete the ligand exchange. Add a large amount of methanol to precipitate the quantum dots again and dry to obtain quantum dot solid.
[0077] Ink preparation: Weigh the quantum dot solid, add dipropylene glycol diacrylate, and prepare a quantum dot concentrate with a solid content of 65% for storage. When it is used, add the acrylate mixture to adjust the viscosity to prepare the quantum dot ink. The acrylate mixture contains substances in order of mass percentage, which are 40% dipropylene glycol diacrylate, 35% quantum dots, 10% tetrahydrofuran acrylate, 9.5% 2-phenylethyl acrylate, 5% titanium dioxide, and 0.5% TPO.
[0078] Ink curing: The quantum dot ink is printed on white glass by a piezoelectric induction-on-demand printer, and the thickness is adjusted to 10μm. It is sent to a nitrogen glove box for ultraviolet light irradiation (365nm), and the curing is completed after irradiation for 1 minute to obtain a quantum dot layer. The top layer of the sample is encapsulated with a transparent resin by dip coating to encapsulate the quantum dot layer and obtain a quantum dot device.
[0079] Example 2
[0080] First ligand:
[0081] ;
[0082] Secondary ligand:
[0083] and mono-2-(methacryloyloxy)ethyl maleate (CAS No. 51978-15-5).
[0084] Comparative Example 1
[0085] The difference from Example 1 is that only a second ligand is contained, and the type of the second ligand is the same as that in Example 1.
[0086] Comparative Example 2
[0087] The difference from Example 1 is that only the first ligand is contained, and the type of the first ligand is the same as that of Example 1.
[0088] Comparative Example 3
[0089] The difference from Example 1 is that it only contains the second ligand:
[0090] .
[0091] Comparative Example 4
[0092] The difference from Example 1 is that only the second ligand: methacryloyloxyethyl succinate is contained.
[0093] Comparative Example 5
[0094] The first ligand is the same as in Example 1.
[0095] The second ligand is only:
[0096] ;
[0097] The rest is the same as in Example 1.
[0098] Comparative Example 6
[0099] The first ligand is the same as in Example 1.
[0100] The second ligand was methacryloyloxyethyl succinate only.
[0101] The rest is the same as in Example 1.
[0102] Table 1 shows the relative luminous efficiency changes of each quantum dot device corresponding to Examples 1-2 and Comparative Examples 1-6 over time under blue light (wavelength 450nm, intensity 10000nit.) excitation. The initial luminous efficiency of Example 1 at 0 hours is 100%, and the relative efficiency = luminous efficiency of the example or comparative example / initial luminous efficiency of the example*100%.
[0103] Table 1
[0104] Time Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 0 100 100 100 100 100 100 100 100 144 99.5 99.8 91.3 99.5 56.4 99.3 85.9 92.4 288 98.3 99.9 85.7 99.1 35.7 96.2 80.5 88.9 696 97.1 97.6 79.3 98.9 28.1 93.2 74.6 78.7 864 96.3 98.5 73.8 99.3 17.7 91.9 70.2 75.1 1176 95.4 98.2 69.6 98.5 9.03 89.3 65.3 71.6 1344 93.2 94.4 66.4 98.2 4.01 85.7 60.7 68.9 1488 92.8 90.8 63.8 97.7 2.06 83.1 58.4 67.2 1680 91.7 91.2 60.2 97.2 1.88 77.1 54.1 63.3 2016 90.7 90.3 57.9 97.0 0.639 73.2 45.9 59.9
[0105] Example 3
[0106] Prepare the first ligand compound:
[0107] ;
[0108] The rest is the same as in Example 1.
[0109] Example 4
[0110] Prepare the first ligand compound:
[0111] ;
[0112] The second ligand is the following ligand and methacryloyloxyethyl succinate:
[0113] ;
[0114] The rest is the same as in Example 1.
[0115] Example 5
[0116] The first ligand is the same as in Example 4;
[0117] The second ligand is:
[0118] and methacryloyloxyethyl succinate.
[0119] The rest is the same as in Example 1.
[0120] Example 6
[0121] The difference from Example 1 is that the quantum dots are green CdSe / ZnSe / ZnS (PL peak wavelength: 535 nm, half-peak width 19.4 nm, and the initial ligand is oleic acid).
[0122] Example 7
[0123] The difference from Example 3 is that the quantum dots are green quantum dots, and the quantum dot material information is the same as Example 6.
[0124] Example 8
[0125] The difference from Example 4 is that the quantum dots are green quantum dots, and the quantum dot material information is the same as Example 6.
[0126] Example 9
[0127] The difference from Example 5 is that the quantum dots are green quantum dots, and the quantum dot material information is the same as Example 6.
[0128] Example 10
[0129] Prepare the first ligand compound:
[0130]
[0131] Others are the same as in Example 1
[0132] Embodiment 11
[0133] Prepare the first ligand compound:
[0134] .
[0135] The rest is the same as in Example 1.
[0136] Table 2-4 shows the changes in relative luminous efficiency of each quantum dot device corresponding to Examples 3-11 over time under excitation of blue light (450nm, intensity of 10000nit).
[0137] Table 2
[0138] Time Example 3 Example 4 Example 5 0 100 100 100 168 99.3 99.5 99.2 336 99.6 98.7 99.0 504 98.3 99.0 98.8 840 97.5 99.1 97.7 1176 98.0 98.3 95.6 1344 95.9 98.9 94.8 1680 93.5 98.0 93.7 1848 92.8 97.1 89.9 2016 91.0 97.6 88.3
[0139] Table 3
[0140] Time Example 6 Example 7 Example 8 Example 9 0 100 100 100 100 144 96.1 94.3 97.7 93.1 336 94.9 93.9 97.1 88.4 576 91.2 90.4 95.1 87.7 840 88.8 89.2 95.8 85.9 1152 86.9 87.5 94.9 84.9 1512 85.0 85.5 93.8 84.3 1728 84.7 84.9 94.2 84.0 2016 84.7 84.0 93.2 83.3
[0141] Table 4
[0142] Time Example 10 Embodiment 11 0 100 100 144 98.1 99.0 288 97.0 98.0 696 96.5 96.9 864 95.9 96.3 1176 94.0 95.8 1344 92.2 94.7 1488 92.0 93.0 1680 89.9 91.1 2016 88.1 90.3
[0143] Table 5 shows the maximum luminous efficiency (referred to as the maximum luminous efficiency) of each quantum dot device corresponding to the embodiments and comparative examples before aging (initial luminous efficiency, referred to as initial luminous efficiency) and during the aging time under aging conditions (450nm, intensity of 10000nit).
[0144] Table 5
[0145] serial number Ripening time Initial light efficiency% Maximum light efficiency% Example 1 1 67.6 68.3 Example 2 1 64.5 66.4 Example 3 1 67.3 68.1 Example 4 1 68.1 69.1 Example 5 1 68.7 69.0 Example 6 2 61.9 64.7 Example 7 2 62.1 65.3 Example 8 2 62.6 64.9 Example 9 2 62.3 66.0 Example 10 1 67.5 67.9 Embodiment 11 1 62.0 62.9 Comparative Example 1 1 61.9 66.2 Comparative Example 2 17 11.3 68.7 Comparative Example 3 2 68.6 69.2 Comparative Example 4 2 45.1 60.7 Comparative Example 5 2 66.5 68.9 Comparative Example 6 6 45.3 65.5
[0146] The change in fluorescence efficiency is the most important performance manifestation of quantum dot devices. When quantum dot ink is prepared into quantum dot devices for use, the fluorescence efficiency needs to reach the highest point immediately on the one hand, and on the other hand, it needs to remain stable during the long-term lighting of the device. As can be seen from the above table, Example 4 has the highest initial light efficiency. After 2000 hours of excitation with 450nm, 10000nit blue light, it can still maintain 97.6% of the maximum efficiency. This value is referred to as "fluorescence efficiency retention rate" in the following text. Example 1 is slightly worse than Example 4. The reason may be that Example 4 uses a larger number of ligand saturated carbons, and the ink is more stable after curing.
[0147] Comparing Example 1 with Comparative Example 1, Comparative Example 1 lacks phosphate ligands, and the sample has a aging time of 1h, and both the initial light efficiency and the maximum light efficiency have decreased. After 2000 hours of excitation, the fluorescence efficiency retention rate is 57.9%. This shows that the stability of quantum dots decreases after the ink is cured due to the lack of phosphate ligands. Comparing Example 1 with Comparative Example 2, Comparative Example 2 only has phosphate ligands, and the sample has a suspended animation phenomenon after curing. The initial light efficiency is only 11.3%, and the maximum light efficiency can only be reached after 17 hours of illumination. The time from the initial light efficiency to the maximum light efficiency is called the "aging time", and the shorter the aging time, the better.
[0148] Comparing Example 1 with Comparative Example 2, the fluorescence efficiency retention rate of Comparative Example 2 after 2000h is 97%. The phenomenon of fluorescent pseudo-death may be due to the fact that when the phosphate ligand is exchanged with the ligand, the phosphate group is easily radicalized, thereby affecting the fluorescence performance of the quantum dots. After high-intensity blue light irradiation, these phosphate groups obtain energy and react with other unsaturated groups in the ink to form a stable structure, thereby improving the fluorescence efficiency retention rate. Therefore, the phosphate ligand is beneficial to the fluorescence efficiency retention rate, and the key lies in how to improve the initial light efficiency and shorten the aging time.
[0149] Comparing Example 1 with Comparative Example 3, Comparative Example 3 only has thiol ligands, and the initial efficiency of the sample is a high 58.6%, but the sample fluorescence efficiency retention rate is only 0.639%, and the quantum dots are almost completely ineffective. This may be because the thiol ligands can stably bind to the surface of the quantum dots when there is no blue light irradiation, but under long-term blue light irradiation, the thiol ligands slowly fall off the surface of the quantum dots, causing defects in the quantum dots, resulting in a low fluorescence efficiency retention rate.
[0150] Comparing Example 1 with Comparative Example 4, Comparative Example 4 only has methacryloyloxyethyl succinate, the initial efficiency of the sample is 45.1%, the maximum efficiency is 50.7%, and the sample fluorescence efficiency retention rate is 73.2%. The carboxyl group in methacryloyloxyethyl succinate interacts worse with quantum dots than the phosphate group and the thiol group, and the ligand exchange time is longer. After the ligand exchange, the fluorescence efficiency of the quantum dots is low, which may be due to the short ligand structure containing only 10 carbon atoms, making the quantum dots less dispersible in acrylate. However, the double bond part of methacryloyloxyethyl succinate that has no effect on quantum dots can be used as an anchor point for the phosphate ligand in Example 1, so that the ligand is stably fixed on the surface of the quantum dots, improving the fluorescence efficiency retention rate.
[0151] Comparing Example 1 with Comparative Example 5, the ligand type lacks methacryloyloxyethyl succinate, the initial efficiency decreases slightly, and the fluorescence efficiency retention rate decreases from 90.7% to 45.9%. Comparing Example 1 with Comparative Example 6, the ligand type lacks thiol ligands, the initial efficiency decreases significantly, and the fluorescence efficiency retention rate is 59.9%. This shows from the side that the first ligand and the second ligand containing two substances can work together to better improve the initial fluorescence efficiency and fluorescence efficiency retention rate of quantum dot devices.
[0152] Comparing Example 1 with Example 2, the methacryloyloxyethyl succinate in Example 2 was replaced with maleic acid mono-2-(methacryloyloxy)ethyl ester, and an unsaturated carbon-carbon double bond was added next to the carboxyl group that interacts with the quantum dots. The performance of Example 2 was lower than that of Example 1, and the price of maleic acid mono-2-(methacryloyloxy)ethyl ester was also higher than that of methacryloyloxyethyl succinate, but the effect was better than that of the comparative example.
[0153] The various properties of Example 3 are slightly worse than those of Example 1, which may be due to the fact that the number of saturated carbons in the ligand used in Example 3 is one less than that in Example 1. Compared with Example 1, the maximum efficiency of Example 5 is improved, which may be due to the ether bond added in the ligand, which improves the dispersibility of the quantum dots in the ink and thus improves the fluorescence performance. However, the fluorescence efficiency retention rate of Example 5 deteriorates, indicating that the presence of the ether bond reduces the stability of the device.
[0154] Examples 6, 7, 8, and 9 used the ligands of Examples 1, 3, 4, and 5 respectively. The change trend of each green quantum dot example was the same as that of the red quantum dots. However, since the green quantum dots were smaller in size than the red quantum dots, the overall sample stability was worse than that of the red quantum dot devices.
[0155] In Example 1, when the phosphate group was replaced by the phosphite group, the fluorescence efficiency retention rate decreased. This may be because the structural stability of the phosphite group after curing is worse than that of the phosphate group.
[0156] In comparison between Example 10 and Example 11, a benzene ring structure is added to the acrylate oligomer part of the ligand, and both the initial fluorescence efficiency and the maximum fluorescence efficiency are reduced. This may be due to the π-π conjugation of the benzene ring on the ligand, which causes the agglomeration of quantum dots, resulting in a decrease in the dispersion of quantum dots in the ink, thereby reducing the fluorescence efficiency.
[0157] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A quantum dot, characterized in that: The quantum dot includes a first ligand and a second ligand; the first ligand is selected from one or both of phosphate acrylate and phosphite acrylate, the phosphate acrylate is shown in Chemical Formula 1, and the phosphite acrylate is shown in Chemical Formula 2; the second ligand includes compounds represented by Chemical Formula 3 and Chemical Formula 4; [Chemical formula 1] ; [Chemical formula 2] ; [Chemical formula 3] ; [Chemical formula 4] ; At least one of R1, R2, and R3 includes a polymer of a first acrylate, at least one of R4 and R5 includes a polymer of a second acrylate, R6 includes a polymer of a third acrylate, R7 is a group containing at least one ester bond, and the number of carbon atoms of R7 is 6 to 20; the number of units of the first acrylate polymer, the second acrylate polymer, and the third acrylate polymer are independently selected from 2 to 10.
2. The quantum dot according to claim 1, characterized in that The raw materials for preparing the phosphate acrylate include: a phosphate with at least one hydroxyl group, or phosphorus pentoxide or phosphorus oxychloride, a monoacrylate containing one hydroxyl group, and a monoacrylate without other active functional groups; the raw materials for preparing the phosphite acrylate include: a phosphite monoester with at least one hydroxyl group, or phosphorus trichloride or phosphorous acid, the monoacrylate containing one hydroxyl group, and the monoacrylate without other active functional groups.
3. The quantum dot according to claim 2, characterized in that The monoacrylate containing one hydroxyl group is selected from one of propylene glycol monoacrylate, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 5-hydroxypentyl acrylate, and 2-hydroxyethyl acrylate; the monoacrylate without other active functional groups is selected from one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, isopropyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, propyl 2-methacrylate, butyl methacrylate, isobutyl methacrylate, lauryl methacrylate, tetrahydrofuranyl acrylate, 2-phenylethyl acrylate, 2-ethoxyethyl acrylate, glycidyl methacrylate, polyethylene glycol acrylate with a number average molecular weight of 200 to 400, ethoxyethoxyethyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, 1-adamantyl acrylate, 4-ethylphenyl acrylate, and 3-methoxybutyl acrylate.
4. The quantum dot according to claim 1, characterized in that At least one of R1, R2, and R3 is a H atom, or R4 is a H atom.
5. The quantum dot according to claim 1, characterized in that The organic matter of the chemical formula 4 is selected from one or more of methacryloyloxyethyl succinate, acrylic acid dimer, mono(2-acryloylethyl ether)succinic acid, and mono-2-(methacryloyloxy)ethyl maleate.
6. The quantum dot according to claim 1, characterized in that The molecular weights of the first ligand and the second ligand are independently selected from 200 to 2000; preferably, the quantum dots are cadmium-free quantum dots.
7. A quantum dot composition, characterized in that The quantum dot composition comprises quantum dots, and the quantum dots are the quantum dots described in any one of claims 1 to 6.
8. The quantum dot composition according to claim 7, characterized in that The quantum dot composition further includes an acrylate monomer, and the mass fraction of the quantum dots is 20-60%.
9. The quantum dot composition according to claim 8, characterized in that The quantum dot composition further comprises a photoinitiator or a thermal initiator. Preferably, the viscosity of the quantum dot composition at 30° C. is less than 25 cP.
10. A display panel, characterized in that: The display panel comprises a quantum dot layer, and the quantum dot layer is formed by curing the quantum dot composition according to any one of claims 7 to 9.
Citation Information
Cited By
Quantum dot light-emitting diode based on functional layer interface photo-crosslinking modification and preparation method thereof
CN122318475A